2016
DOI: 10.1364/oe.24.00a781
|View full text |Cite
|
Sign up to set email alerts
|

Sensing atmospheric reactive species using light emitting diode by incoherent broadband cavity enhanced absorption spectroscopy

Abstract: We overview our recent progress in the developments and applications of light emitting diode-based incoherent broadband cavity enhanced absorption spectroscopy (LED-IBBCEAS) techniques for real-time optical sensing chemically reactive atmospheric species (HONO, NO3, NO2) in intensive campaigns and in atmospheric simulation chamber. New application of optical monitoring of NO3 concentration-time profile for study of the NO3-initiated oxidation process of isoprene in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…IBBCEAS has been rapidly developed since Fiedler et al (2003) first described it in 2003. More recently, the technology has been successfully applied to measure a variety of trace gases (Min et al, 2016;Wang et al, 2017;Yi et al, 2016;Volkamer et al, 2015), weakly absorbed cross sections of different trace gases (Chen and Venables, 2011;Kahan et al, 2012) and aerosol extinction (Washenfelder et al, 2013). Using a xenon arc lamp as a light source, Washenfelder et al (2008) reported the first measurement of glyoxal using the IBBCEAS technique in the laboratory with a detection limit of 58 pptv (2σ ) within 1 min.…”
Section: Introductionmentioning
confidence: 99%
“…IBBCEAS has been rapidly developed since Fiedler et al (2003) first described it in 2003. More recently, the technology has been successfully applied to measure a variety of trace gases (Min et al, 2016;Wang et al, 2017;Yi et al, 2016;Volkamer et al, 2015), weakly absorbed cross sections of different trace gases (Chen and Venables, 2011;Kahan et al, 2012) and aerosol extinction (Washenfelder et al, 2013). Using a xenon arc lamp as a light source, Washenfelder et al (2008) reported the first measurement of glyoxal using the IBBCEAS technique in the laboratory with a detection limit of 58 pptv (2σ ) within 1 min.…”
Section: Introductionmentioning
confidence: 99%
“…Cavity-enhanced absorption spectroscopy (CEAS) is based on the use of optical resonant cavities in order to enhance light interaction with a gas species inside the cavity (Gherman and Romanini, 2002;He et al, 2018;Yi et al, 2016). In CEAS setups, a proper locking between the laser wavelength and the cavity resonance mode must be carried out via two approaches: (i) the cavity length is controlled by a piezo transducer (PZT) for the resonance mode to follow laser wavelength; and (ii) the length of the cavity is fixed, and the laser wavelength is locked to the cavity resonance mode.…”
Section: Introductionmentioning
confidence: 99%
“…With an integration time of < 1.5 s, a detection limit of ~3 ppb was achieved by using direct absorption spectroscopy (DAS) and a multi-pass cell with a 54.6 m optical path length. Compared to a multi-pass gas cell, a F-P cavity is simple in structure, easy to adjust, low in attenuation and small in volume [13][14][15][16]. The Pound-Drever-Hall (PDH) technique was used to frequency stabilize the excitation laser to the cavity, which was successfully demonstrated on laser frequency stabilization of various wavelengths [17][18][19].…”
Section: Introductionmentioning
confidence: 99%